2017
DOI: 10.1002/pros.23434
|View full text |Cite
|
Sign up to set email alerts
|

The unidirectional hypoxia‐activated prodrug OCT1002 inhibits growth and vascular development in castrate‐resistant prostate tumors

Abstract: These studies provide the first evidence that OCT1002 can be an effective agent in treating hypoxic, castrate-resistant prostate tumors, either singly or in combination with established chemotherapeutics for prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…OCT1002 has shown significant anti-cancer activity in prostate cancer models in which hypoxia has been confirmed, 118,123 demonstrating growth inhibition and suppression of metastasis. This aligns with earlier in vivo studies with AQ4N that have shown anti-angiogenic 124,125 and anti-metastatic activities.…”
Section: Oct1002mentioning
confidence: 99%
“…OCT1002 has shown significant anti-cancer activity in prostate cancer models in which hypoxia has been confirmed, 118,123 demonstrating growth inhibition and suppression of metastasis. This aligns with earlier in vivo studies with AQ4N that have shown anti-angiogenic 124,125 and anti-metastatic activities.…”
Section: Oct1002mentioning
confidence: 99%
“…OCT1002, a deuterated analog of AQ4N, was not only able to inhibit LNCaP, 22Rv1, and PC3 tumor growth and revascularization but could also enhance the antitumor synergistic effects with other chemotherapeutic agents. 56,57 Synergistic liposomes containing both hypoxia-activated AQ4N and photosensitizer chlorin e6 have been introduced in hypoxic tumor therapy, in which hypoxia induced by photosensitizer chlorin e6 in PDT was used to subsequently trigger AQ4N activation. 58 Shen et al investigated AQ4N and gossypol combination chemotherapy in HA@AQ4N-Cu(II)-gossypol NPs and demonstrated that AQ4N could function as self-carrier material and auto-fluorescence indicator.…”
Section: N-oxidesmentioning
confidence: 99%
“…Mitoxantrone (MTX; Novantrone®), (1,4‐dihydroxy‐5,8‐bis[[2‐[(2‐hydroxyethyl)amino]ethyl]amino]‐9,10‐anthracenedione) is a anthracenedione—structurally related to the classical anthracyclines. MTX has also provided an impetus for the generation of derivatives including prodrug forms for a more selective targeting of tumor cell populations . Its behavior in the chromatin environment is an exemplar of multi‐level action .…”
Section: One Man's Probe Is Another Man's Poisonmentioning
confidence: 99%